PENDAMPINGAN MANAJEMEN PAKAN PADA BUDIDAYA NILA SISTEM BIOFLOK DI BATAM UNTUK PENINGKATAN PRODUKSI - Laksmi Sulmartiwi; Woro Hastuti Satyantini; Kustiawan Tri Pursetyo; M. Rafly Nur Wahyu Dwi Saputra; Intan Fajriya Mardiana; Puji Dwi Martianasari; Cicik Kurniawati (Universitas Mataram, 2026)
This community service program was carried out to enhance the knowledge and skills of fish farmer groups (POKDAKAN) in Batam City in implementing the biofloc system efficiently through feed management and probiotic application. Batam City has substantial potential for Nile tilapia aquaculture; however, challenges such as high feed costs and declining water quality remain major constraints. The biofloc system offers a solution by utilizing microorganisms to convert organic waste into supplemental feed, thereby reducing production costs and maintaining water quality. The objective of this community service program is to improve the partners’ understanding and competencies in feed management and probiotic application. It is expected that the adoption of this technology will address the partners’ challenges, increase productivity, and ultimately enhance their income. The methods employed in this program included counseling, demonstrations, and hands-on practice related to probiotic application and the measurement of water quality parameters in culture ponds. Evaluation results showed that 80% of participants understood the biofloc technology, 65% were able to form and maintain flocs, and 80% recognized its benefits for aquaculture. Participants also reported increased knowledge regarding floc management, probiotics, and water quality parameters that were previously not well understood. The training strengthened participants’ understanding of the importance of controlling temperature, pH, dissolved oxygen (DO), and ammonia in supporting Nile tilapia growth within a biofloc system. Field practice activities received very positive responses and encouraged more effective implementation of biofloc technology among fish farmers in Batam. Therefore, continued assistance and systematic monitoring are necessary to ensure optimal application of biofloc technology and to provide long-term benefits for the aquaculture community.